Upaya Meningkatkan Kemampuan Membaca Melalui Permainan Kartu Bergambar Pada Siswa Kelas I SDN Cidokom 02 - Efendi, Sirman Efendi (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2022)
Grade I students Most of the students have not been able to understand/master the forms of letters, so they still have difficulty distinguishing and using letters. they back off. Starting from the implementation of Indonesian language learning using picture media to overcome the difficulties of learning to read beginning for first graders. Letter cards are media or tools in achieving success in teaching given by teachers to students. Learning through letter cards is an interaction between students that is carried out consciously and planned to improve students' abilities which are determined by learning outcomes. This study uses classroom action research in collaboration with peers. The main purpose of this classroom action research is to solve real problems in the classroom, which not only aims to solve the problem, but at the same time find answers to why it can be solved through the actions taken. This research was jointly developed by researchers and collaborators to determine policy and development. The variables of this study consisted of two variables, namely the independent variable and the dependent variable. The independent variable of this research is word card media technique and the dependent variable of this research is word reading. Classroom action research is a process of activities carried out in the classroom. Based on observations and recording of the learning process and learning outcomes, information was obtained that the first grade students of SD Negeri 02 Cidokom were several students where most of the students had not been able to understand/master the forms of letters, so they still had difficulty distinguishing and using them in reverse.